MISKONSEPSI SISWA SD PADA MATERI PHYSICAL PROCESSES: SEBUAH STUDI KASUS - Yogi Kuncoro Adi; Ndaru Mukti Oktaviani (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2019)
Understanding the concept has a vital role in the scientific literacy of primary school students. The qualitative case study used in this study as a method to reveal the misconceptions types of primary school students in science, especially Physical processes. The results show that primary school students have a variety of misconceptions in forces, floating-sinking, light, electricity and magnetism, and the Earth and space. Based on the findings of the study, further research is recommended to understand student learning processes and misconceptions remediate using cognitive conflict.